Epidemiological Study of Acute Hepatitis A and C in Karbala Province from 2016-2020 - Mohammed, Yaseen Kadhim; Shaalan, Maytham Hadi; Ebrahim, Yageen Khalid; Ali, Hibat Niema; Hamza, Hind Kazar; AL Kareem, Fatima Abid (Journal of Science in Medicine and Life, 2024)
Viral disease is one of infectious that caused by viruses and cause harm to liver . and may be the harm permanents or temporary . characteristic by presences inflammatory cells with in liver tissue and it is happened when an organism's body is infected by pathogenic hepatitis viruses, and invaded virus particles attach to and enter susceptible cell. [1]